Fructobacillus apis sp. nov., isolated from the gut of honeybee (Apis mellifera). Issue 11 (24th November 2022) - Chen, Yi-sheng; Wang, Li-Ting; Lin, Shih-Ting; Lee, Yun-Shien; Chang, Yu-Chung; Wu, Hui-Chung; Liao, Chia-Yu; Chen, Wei-Hua; Deng, Jin-Nan; Wang, Yu-Hsuan
Abstract : A Gram-positive, facultatively anaerobic, catalase-negative, fructose-dependent strain (W13 T ) was isolated from the gut of honeybee ( Apis mellifera ). Phylogenetic analysis based on 16S rRNA gene sequencing indicated that strain W13 T represents a distinct line of descent within the genus Fructobacillus, with the closest neighbours being Fructobacillus broussonetiae BCRC 81240 T (98.9 % sequence similarity) and Fructobacillus durionis DSM 19113 T (96.8 % sequence similarity). Comparative sequencing of the additional phylogenetic markers rpoC and recA confirmed the 16S rRNA gene tree topology. The complete genome of strain W13 T consisted of 1 292 712 bp with a G+C content of 48.3 mol%. Pairwise comparisons of the average nucleotide identity values and digital DNA–DNA hybridization values between the genomes of W13 T and its close phylogenetic neighbours, F. broussonetiae BCRC 81240 T and F. durionis DSM 19113 T, resulted in 76.2–84.1 % and 20.2–27.6 %, respectively. The main cellular fatty acids of strain W13 T were C16 : 0, C18 : 1 ω 9 c and C18 : 1 ω 7 c . Thus, we propose a novel species within the genus Fructobacillus, with the name Fructobacillus apis sp. nov. and the type strain is W13 T (= NBRC 115637 T =BCRC 81365 T ).